RESERVOIR AGES IN BALTIC SEA SEDIMENT-A CASE STUDY OF AN ISOLATION SEQUENCE FROM THE LITORINA SEA STAGE - Hedenstrom A.; Possnert G. (My University, 2001)
In order to quantify the reservoir age in Baltic Sea sediment, one sedimentary sequence from an isostatically isolated basin was subject to high-resolution AMS radiocarbon dates. Diatom analysis confirmed deposition during the Litorina Sea stage and later, in a freshwater lake. Macrofossils from well preserved seeds and other remnants from terrestrial plants were used for AMS datings. It is assumed that these fragile plant remains are not redeposited or affected by internal ages. The ages obtained from the macrofossils range from 6460+/-125 to 5580+/-75 14CyrBP. By comparing these radiocarbon ages with those obtained by bulk sediment dates, it was obvious that the bulk samples were affected by reservoir ages, resulting in too old ages. The reservoir ages varied within the sediment column; during the most saline phase, the reservoir age was approximately 750yr, shortly after the isolation ca 400yr and in the freshwater lake, the age differences between the two series were neglectable.